2012
DOI: 10.1093/jxb/ers298
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dynamics and MET1a-like gene expression changes during stress-induced pollen reprogramming to embryogenesis

Abstract: Stress-induced plant cell reprogramming involves changes in global genome organization, being the epigenetic modifications key factors in the regulation of genome flexibility. DNA methylation, accomplished by DNA methyltransferases, constitutes a prominent epigenetic modification of the chromatin fibre which is locked in a transcriptionally inactive conformation. Changes in DNA methylation accompany the reorganization of the nuclear architecture during plant cell differentiation and proliferation. After a stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 54 publications
9
106
0
Order By: Relevance
“…Although application of n-butanol following cold pretreatment did not elevated further the embryo/callus ratio, this combined treatment resulted in a higher number of responding microspores compared to cold treatment alone. These results suggest that cytoskeletal reorganization induces developmental program shift from the gametophytic to the sporophytic pathway, but gene expression changes or epigenetic alterations induced by cold stress (Solís et al 2012) ensure a more efficient induction of embryogenesis instead of generating callus.…”
Section: Effect Of N-butanol On Cortical Microtubule Arraymentioning
confidence: 92%
“…Although application of n-butanol following cold pretreatment did not elevated further the embryo/callus ratio, this combined treatment resulted in a higher number of responding microspores compared to cold treatment alone. These results suggest that cytoskeletal reorganization induces developmental program shift from the gametophytic to the sporophytic pathway, but gene expression changes or epigenetic alterations induced by cold stress (Solís et al 2012) ensure a more efficient induction of embryogenesis instead of generating callus.…”
Section: Effect Of N-butanol On Cortical Microtubule Arraymentioning
confidence: 92%
“…There is increasing evidence that numerous processes of development and differentiation in both plants and animals are accompanied by chromatin remodeling [Kouzarides, 2007]. Stress-induced plant cell reprogramming involves changes in global genome organization, the epigenetic modifications being key factors of genome flexibility [Arnholdt-Schmitt, 2004;Solís et al, 2012].…”
mentioning
confidence: 99%
“…The past decade revealed exciting findings on epigenetic mechanisms controlling developmental processes specific to flowering plants: the determination of the sporogenic fate during development, the differentiation of gametes within multicellular gametophytes, and the distinction of the 2 male gametes involved in double fertilization [Twell, 2011]. Recent studies have demonstrated epigenetic changes during plant developmental processes and after microspore induction to the sporophytic pathway leading to embryogenesis [Solís et al, 2012;Testillano et al, 2013]. However, the knowledge of the DNA methylation regulation during microspore embryogenesis is very limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These events include structural and cellular changes during the first divisions (Dubas et al 2011;Hause et al 1993;Satpute et al 2005;Telmer et al 1995;Zaki and Dickinson 1990), changes in DNA synthesis and gene expression (Binarova et al 1993;Boutilier et al 1994;Hays et al 1999;Seguí-Simarro et al 2011a), the role of epigenetic modifications Rodríguez-Sanz et al 2014;Solís et al 2012), regulatory cascades ( (Cordewener et al 2000;Cordewener et al 1994;Pechan et al 1991), with special focus on heat-shock proteins expression (Cordewener et al 1995;Seguí-Simarro et al 2003;Testillano et al 2000;Zhao et al 2003). Comparative studies between MDEs and zygotic embryos (Ilic-Grubor et al 1998;Yeung et al 1996) have shown that MDEs may hold a high morphologic similarity to zygotic embryos, and they can be used as a model to study general embryogenesis characteristics, as well as the role of different plant hormones during embryogenesis initiation and embryo development (Belmonte et al 2010;Hays et al 2001;Hays et al 2000;Hays et al 2002;Robert et al 2015).…”
Section: Dh36 Embryogenic Response Approaches That Of the Model Speciesmentioning
confidence: 99%